Implementation of Caning Punishment in Nanggroe Aceh Darussalam Province in a Human Rights Approach - Taufiki, Muhammad; Albani, Sonifah; Kamarusdiana, Kamarusdiana (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The Nanggroe Aceh Darussalam Provincial Government is one of the regions that has special autonomy. This is as regulated in Law Number 11 of 2006 concerning the Government of Aceh. The Islamic criminal law that emerged in Aceh is different from criminal law in general. Among the applications of criminal law in Aceh is caning. There is a conflict between the Aceh Qanun regarding the Jinayat law and the Governor's Regulation regarding the application of the caning law. Initially carried out in an open place (mosque courtyard), it was then moved to a closed place, namely a correctional institution. The research method used in this research is a qualitative method with an empirical approach and a statutory regulatory approach. The results of the research state that the transfer of caning punishment has been in the spotlight since this regulation was discussed until the publication of this legal product. So there needs to be a more in-depth and comprehensive study in order to find the best solution in enforcing Islamic criminal law.